Solutions like excitations in the one-dimensional electrical transmission line - Pelap, F.B.; Faye, M.M. (Нелінійні коливання, 2005)
Dynamics of modulated waves are studied in the one-dimensional discrete nonlinear electrical transmission line. Contribution of the linear dispersive capacitance is appreciated and it is shown via a reductive
perturbation method that evolution of such waves in this system is governed by a higher order nonlinear
Schrodinger equation. Passing through the Stokes analysis, a generalized criterion for the Benjamin ¨ – Feir
instability in the network is established and the exact solutions of the obtained wave equation are determined by the means of the Pathria and Morris’s approach. Вивчається динамiка модульованої хвилi в одновимiрнiй дискретнiй нелiнiйнiй лiнiї електропередач. Враховано внесок лiнiйної дисперсiйної ємностi та показано за допомогою методу редуктивного збурення, що еволюцiя таких хвиль у системi описується нелiнiйним рiвнянням Шрьодiнгера вищого порядку. За допомогою методу Стокса встановлено узагальнений критерiй нестiйкостi за Бенджамiном– Фейрi у мережi i знайдено точнi розв’язки хвильового рiвняння за
методом Патрiа та Моррiса.